Organisational and Strategic Communication Research: European Perspectives II - Melo, Ana Duarte (2015)
This e-book presents a selection of the research papers presented at the 5th European Communication Research and Education Association (ECREA) Conference in Lisbon, November, 2015. The book reflects the work of researchers within the Organisational and Strategic Communication (OSC) Section of ECREA from different backgrounds and higher education institutions in Europe and highlights the diverse professional and scientific interests of the Section.